Evaluation of Whole-Genome Sequence, Genetic Diversity, and Agronomic Traits of Basmati Rice (Oryza sativa L.) - Kishor, D.S.; Seo, Jeonghwan; Chin, Joong Hyoun; Koh, Hee-Jong (Frontiers in Genetics, 2020)
Basmati is considered a unique varietal group of rice (Oryza sativa L.) because of its aroma and superior grain quality. Previous genetic analyses of rice showed that most of the Basmati varieties are classified into the aromatic group. Despite various efforts, genomic relationship of Basmati rice with other varietal groups and genomic variation in Basmati rice are yet to be understood. In the present study, we resequenced the whole genome of three traditional Basmati varieties at a coverage of more than 25X using Illumina HiSeq2500 and mapped the obtained sequences to the reference genome sequences of Nipponbare (japonica rice), Kasalath (aus rice), and Zhenshan 97 (indica rice). Comparison of these sequences revealed common single nucleotide polymorphisms (SNPs) in the genic regions of three Basmati varieties. Analysis of these SNPs revealed that Basmati varieties showed fewer sequence variations compared with the aus group than with the japonica and indica groups. Gene ontology (GO) enrichment analysis indicated that SNPs were present in genes with various biological, molecular, and cellular functions. Additionally, functional annotation of the Basmati mutated gene cluster shared by Nipponbare, Kasalath, and Zhenshan 97 was found to be associated with the metabolic process involved in the cellular aromatic compound, suggesting that aroma is an important specific genomic feature of Basmati varieties. Furthermore, 30 traditional Basmati varieties were classified into three different groups, aromatic (22 varieties), aus (four varieties), and indica (four varieties), based on genome-wide SNPs. All 22 aromatic Basmati varieties harbored the fragrant-inducing Badh2 allele. We also performed comparative analysis of 13 key agronomic and grain quality traits of Basmati rice and other rice varieties. Three traits including length-to-width ratio of grain (L/W ratio), panicle length (PL), and amylose content (AC) showed significant (P < 0.05 and P < 0.01) differences between the aromatic and indica/aus groups. Comparative analysis of genome structure, based on genome sequence variation and GO analysis, revealed that the Basmati genome was derived mostly from the aus and japonica groups. Overall, whole-genome sequence data and genetic diversity information obtained in this study will serve as an important resource for molecular breeding and genetic analysis of Basmati varieties.